Controversy as Marketing Strategy: Indonesian Celebrities Promoting Skincare through Public Image Polarization - Elfina Okto Posmaida Damanik; Mahaitin H Sinaga; Jusra Tampubolon; Hengki Mangiring Parulian Simarmata (Fakultas Ekonomi Universitas Simalungun, 2025)
This study aims to determine the impact of controversial figures in marketing strategies in the skincare industry. The research focuses on three public figures: Nikita Mirzani, Dr. Richard Lee, and “Dokter Detektif.